PESAN DAKWAH DALAM FILM “AIR MATA DI UJUNG SAJADAH” - Hafifah Intan Rahmadiani; Nazar; Siti Misbah; Fadillah Ulfa (JOISCOM (Journal of Islamic Communication), 2025)
Dakwah messages are those that encompass the principle of Amar Ma’ruf Nahi Mungkar. Utilizing evolving technology, such as audiovisual media in films, is an effective means of conveying dakwah. This study aims to explain the content of dakwah messages in the film "Air Mata Di Ujung Sajadah." The theories applied in this research are Endang Saifuddin Anshari's theory of dakwah messages and Krippendorff's content analysis theory. The research employs a descriptive qualitative approach with content analysis methods. The data sources include documentation from the film "Air Mata Di Ujung Sajadah" and relevant articles, theses, dissertations, films, and literature. The results show that there are 13 scenes in the 103-minute film that encompass three categories of dakwah messages: Aqidah, Sharia, and Akhlaq. First, in the Aqidah category, there are messages about faith in Allah (SWT). Second, in the Sharia category, there are messages about performing prayers, supplication, recitation, and caring for children. Third, in the Akhlaq category, there are messages about respecting parents, patience and sincerity, building good relationships, and forgiveness. Keywords: Dakwah Messages, and Film "Air Mata Di Ujung Sajadah".